IMMU-13. A FAILURE TO RESOLVE INFLAMMATION: ROLE OF RESOLVINS IN THE TREATMENT OF PEDIATRIC CNS TUMORS. Issue 2 (22nd June 2018) - Clymer, Jessica; Barksdale, Chantal; Chang, Jaimie; Kieran, Nicholas; Sulciner, Megan; Colas, Romain; Bandopadhayay, Pratiti; Huang, Sui; Serhan, Charles; Panigrahy, Dipak; Kieran, Mark
Abstract: BACKGROUND: Current brain tumor therapies are focused on reducing tumor burden by inducing apoptotic and necrotic tumor cells. However, inflammation in the tumor microenvironment caused by this debris can accelerate tumor progression. Inflammation is endogenously regulated resolvins and protectins, molecules that are biosynthesized and act in the brain and cerebrospinal fluid. They clear cellular debris via local macrophages while reducing localized inflammatory cytokines. We hypothesized that control of inflammation through resolvins and protectins could represent a novel treatment modality by pharmacologically promoting the clearance of tumor cell debris by microglia, thereby depriving the surviving tumor cells of inflammatory stimuli. METHODS AND RESULTS: We show that debris generated by killing of either medulloblastoma or glial tumors (using cisplatin chemotherapy, dabrafenib targeted therapy or the epigenetic inhibitors JQ1) stimulate residual live tumor cells to grow. This effect was inhibited by nanogram levels of resolvins/protectins and without toxicity in a variety of tumor types including orthotopic models. The effect was mediated via enhanced macrophage and microglial phagocytosis of tumor cell debris and counter-regulation the secretion of pro-inflammatory cytokines/chemokines, including CCL5, TNFα, CCL2, CXCL1, and CCL4. CONCLUSIONS: We show that resolvins and protectins stimulate the clearance of tumor cell debris by stimulating macrophage and microglial phagocytosis and counter-regulating pro-inflammatory and pro-tumorigenic cytokines. This approach not only has relevance to our current approaches to cancer therapy (focused on maximal tumor cell kill), but may have an impact on the side effects of current immunotherapies where therapy induced inflammation in the tumor results in significant morbidity.